THE THREATENING OF SKOUW LANGUAGE IN JAYAPURA - Paranoan, Emon (DINAMIS, 2021)
The Threatening of Skouw Language in Jayapura. This local research aims mainly to faind out (1) The What factors that threatening the Skouw Language in Jayapura ?This local research takes places in Jayapura particularly in Skow area. The method used descriptive qualitative research the data are in the questionnaire form this study uses the descriptive method and supported by quantitative data. This study used two instruments, namely: observation and questionnaire, as a data collection tool. From the research, a community of Skouw residing in the Skouw Mabo village, Skouw Yambe village and Skouw Sae village, which use Skouw language only the elderly speakers or parents, while the young generation, use the Indonesian language. In general, seen from the results of research, will be extinct in a relatively short period of time when there was no awareness of the native speakers to teach the young generation and local governments, especially in Jayapura city government issued a policy for the preservation of Skouw language, which was one of Papua rich culture.